Effect Of A New Absorber Design On The Performance Of PV/T Collector: Numerical Comparative Study - Abdulameer Sachit, Fadhil; Tamaldin, Noreffendy; Suhaimi, Misha; Lateef Abdullah, Amira; Mohd Rosli, Mohd Afzanizam (Penerbit Akademia Baru, 2020)
The solar energy applications can be roughly divided into two main groups. A photovoltaic is an energy system that transforms solar energy into electric power and thermal energy system called solar collector that transforms solar energy into thermal energy. The photovoltaics performance affected by the high temperature of it is surface that absorbs the solar irradiance and the efficiency drop due to these higher temperatures. Therefore, the two systems associated with each other in the combined system called PV/T to enhance photovoltaic efficiency. The term PV/T (photovoltaic thermal) refers to a solar collector that uses a photovoltaic cell as an integral component of the absorption plate. The high temperature of solar photovoltaic will be decreased and transmitted to the circulated fluid inside the collector tubes. This system produces electrical and thermal at the same time. The solar collector is the vital part of PV/T. Many absorber designs have been developed in the solar collector to enhance the overall performance of the PV/T system. In the present work, a new photovoltaic thermal collector named serpen-direct is designed. Modeling for the new absorber design has been developed and validated. Numerically, PV/T performance for the serpent-direct design is analyzed and compared with the conventional serpentine design by using MATLAB Simulink. The PV and thermal efficiencies were determined under various parameters condition; mass flow rates range from 0.01 kg/s to 0.1 kg/s and solar irradiance values 700 W/m2 and 900 W/m2. Results indicate that the serpendirect flow absorber design achieved a better system overall performance than serpentine design under similar operating conditions. The higher electrical and thermal efficiencies were 14.52%, 55%, respectively, for the PV/T serpen-direct absorber design and 14.43 %, 56.1%, correspondingly, for the serpentine absorber design.